COVID-19 Vaccine Perceptions and Differences by Sex, Age, and Education in 1,367 Community Adults in Ontario - Syan, Sabrina K.; Gohari, Mahmood R.; Levitt, Emily E.; Belisario, Kyla; Gillard, Jessica; DeJesus, Jane; MacKillop, James (Frontiers in Public Health, 2021)
Background: COVID-19 is a global pandemic; vaccination efforts may be impeded by vaccine hesitancy. The present study examined willingness to receive COVID-19 vaccine, the associated reasons for willingness/unwillingness, and vaccine safety perceptions in a cross-sectional assessment of community adults in Ontario. Methods: 1367 individuals (60.6% female,mean age=39.4%) participated in this study between January 15,2021 and February 15,2021. Perceptions of vaccine safety and reasons for willingness/unwillingness to receive the COVID-19 vaccine were investigated using an online assessment. Perceptions were investigated in general and by age, sex and education using analysis of variance. Results: Overall, 82.8% sample reported they were willing to receive a COVID-19 vaccine and 17.2% reported they were unwilling. The three most common reasons for unwillingness were long-term side effects (65.5%), immediate side effects (60.5%), and lack of trust in the vaccine (55.2%). Vaccine willingness significantly differed by sex and education level, with female participants and those with less than a bachelor’s degree being more likely to report unwillingness. Perception of COVID-19 vaccine safety was significantly lower (-10.3%) than vaccines in general and differed by age, sex and education, with females, older adults, and individuals with less than a bachelor’s degree reporting lower perceived COVID-19 vaccine safety. Conclusion: In this sample of community adults, under one in five individuals was unwilling to receive a COVID-19 vaccine, but with higher rates in population subgroups. Targeting public health messaging to females and individuals with less than Bachelor’s degree, and addressing concerns about long-term and immediate side effects may increase vaccine uptake.